Peran Undang-Undang Cipta Kerja dalam Reformasi Hukum Investasi di Indonesia - M. Arif Florisadeg (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
The Job Creation Law which was passed in 2020 is a milestone in investment law reform in Indonesia with the aim of improving the investment climate and increasing the ease of doing business in Indonesia. This journal discusses how the Job Creation Law plays a role in improving investment regulations, overcoming various obstacles faced by investors, and encouraging economic growth. Using a literature study and policy analysis approach, this journal examines the impact of the Job Creation Law on the investment sector in Indonesia, as well as the challenges still faced in its implementation.